A note on a theorem of Sparr - Ameur, Y. (MATHEMATICA SCANDINAVICA, 2004)
We prove that, regardless of the choice of a positive, concave function ψ on R_+ and a "weight function" λ, the weighted _2-space _2(ψ(λ)) is c-interpolation with respect to the couple (_2,_2(λ)), where c≤2. Our main result is that c=2 is best possible here; a fact which is implicit in the work of G. Sparr.